Effects of the redox state on the morphology of the regioregular sexi-3-alkylthiophene - Łapkowski, M; Zak, J; Kolodziej-Sadlok, M; Guillerez, S; Bidan, G (Electrochimica acta, 2001)
The electrochemical properties of solid phase α-monochloro substituted regioregular 3-alkylthiophene consisting of six units of 3-octylthiophene (6OT) were studied in nonaqueous electrolyte solutions using cyclic voltammetry and electrochemical atomic force microscopy (EC AFM). As confirmed by voltammetry, the 6OT molecules in an oxidized form of monocation radical are not subject to consecutive reactions, due to the presence of the α-substituent. In situ AFM images of the thin films of 6OT cast on metal substrates revealed reversible, drastic changes of the film morphology while applied potential was switched between values corresponding to the particular redox state. Dimerization of the oligomers and π-stacks formation is postulated to explain the observed morphology changes in the 6OT films.